Perilaku Konsumerisme Mahasiswa Program Studi AFI FUSI UIN-SU (Tinjauan Praktik Belanja Online di Shopee) - Cindyani, Cindyani; Adenan, Adenan (Lembaga Yasin AlSys, 2023)
Consumerism is an ideology that makes a person or group carry out consumption activities or use goods produced excessively, unconsciously and continuously. Instilling religious values, AFI FUSI UIN-SU students are also instilled with a wise mindset through Islamic philosophy courses as a compulsory subject. This research is a qualitative research type of field study using a philosophical approach. This study aims to identify matters concerning the consumer behavior level of AFI students towards the Shopee Application and the impact of the shopee application on the consumerism behavior of AFI students. The results of this study show that the consumerism behavior of AFI students towards the shopee application has been proven true and is endemic to AFI students to date, The impact of consumer behavior on the shopee application is divided into two, namely positive and negative.